Energy Saving Potential of Public Building in Jiangbei District of Chongqing - He Hua; Long Tian-yu; Zhou Zhi-yong; Zhao Juan (2009 International Conference on Management and Service Science, 2009)
Jiangbei belongs to Metropolitan Advanced Economic Sphere of Chongqing so its character of energy consumption can be very typical in Chongqing. A energy consumption investigation of 72 public buildings was organized by People's Local Congress in Jiangbei. Based on the investigation data and information coming from energy audit and site measurement for 14 public buildings, character of energy consumption for six different types of public building is summed up, and problems and its solutions of six energy consumption systems of public building are analysed also. It was pointed out that electricity is the main form of building energy and building electricity consumption was more than 50% of total electricity consumption in Jiangbei. Also, electricity consumption of public building, among which energy for heating, air conditioning and lighting can be half, is nearly 50% of building electricity consumption. At last, energy saving potential of public building in Jiangbei is evaluated. It is determined that if 289.3 million yuan is invested in energy saving retrofit project of public bulding in Jiangbei, it will create 9,640 work opportunities a year, drive 723.3 million yuan output of other industries and reduce 161,629 tons of CO 2 emission.